A quality by design approach to understand formulation and process variability in pharmaceutical melt extrusion processes. (23rd January 2015) - Patwardhan, Ketaki; Asgarzadeh, Firouz; Dassinger, Thomas; Albers, Jessica; Repka, Michael A.
Abstract: Objectives: In this study, the principles of quality by design (QbD) have been uniquely applied to a pharmaceutical melt extrusion process for an immediate release formulation with a low melting model drug, ibuprofen. Methods: Two qualitative risk assessment tools – Fishbone diagram and failure mode effect analysis – were utilized to strategically narrow down the most influential parameters. Selected variables were further assessed using a Plackett‐Burman screening study, which was upgraded to a response surface design consisting of the critical factors to study the interactions between the study variables. In process torque, glass transition temperature (Tg ) of the extrudates, assay, dissolution and phase change were measured as responses to evaluate the critical quality attributes (CQAs) of the extrudates. The effect of each study variable on the measured responses was analysed using multiple regression for the screening design and partial least squares for the optimization design. Key findings: Experimental limits for formulation and process parameters to attain optimum processing have been outlined. A design space plot describing the domain of experimental variables within which the CQAs remained unchanged was developed. Conclusions: A comprehensive approach for melt extrusion product development based on the QbD methodology has been demonstrated. Drug loading concentrations between 40‐ 48%w/w and extrusion temperature in the range of 90–130°C were found to be the most optimum.